DETERMINANT RENDAHNYA KUNJUNGAN KE POSYANDU LANSIA DI BANTUL YOGYAKARTA - Indriani, I; Fatmawati, Veni (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
Globally, the elderly population is increasing and has increased the risk of non-communicable diseases (NCDs). Posyandu for the elderly is one of the government programs aimed at early detection of NCDs and health promotion. However, the number of visits is still below the national target. Objective: to identify the factors influencing elderly visitation to Posyandu, Bantul region, Yogyakarta. Methods: observational research using a cross sectional approach. In the population of 103 elderly registered in Posyandu Lansia in Bantul area, 66 elderly were sampled with inclusion and exclusion criteria. Data collection using questionnaires, and health checks was carried out by checking blood pressure, anthropometry, and BMI. Data analysis was done in C-Square with SPSS version 19.00. Results: Of the 66 elderly, 40 elderly (60%) did not regularly visit the posyandu. The female population is larger, with 69.7% of those ages 56-65 (37.9%). More than 50% of the elderly only graduated from elementary school (SD), working on farms 34 elderly (51.5%), low income (less than IDR 500,000) 38 elderly (57.6%), have close access to the Posyandu within a radius of <500 meters, namely 44 elderly (66.7%), and there is a relationship between the characteristics, social support, and attitudes of the elderly with visits. Conclusion: Addressing the determinants of low attendance at Posyandu Lansia in Bantul, Yogyakarta is essential to ensuring the well-being and quality of life for the elderly population in the community. It needs to implement community outreach programs and incorporate cultural sensitivity training for healthcare providers.